CHURCH OF ST. THOMAS IN INDIA: Its History, Problems and Hopes - Aykara, Thomas; Chethimattam, John B (Journal of Dharma, 1989)
"Among all the nations of earth there is but one People of God, which takes its citizens from every race, making them citizens of a kingdom which is of a heavenly and not of an earthly nature" (L. G. No. 13). The universality of the Church is not purely extensive seeking to spread itself to all peoples, but also intensive "striving energetically and constantly to bring all humanity with all its riches back to Christ its Head in the unity of His Spirit. In virtue of this catholicity each individual part of the Church contributes through its special gifts to the good of the other parts and of the whole Church" (Ibid). Hence the history, the unique heritage and tradition of the Church of St. Thomas tracing its origin to the preaching of the Apostle of Christ, with its own problems and hopes has a unique contribution to make to the unity and universality of the Church. So we present below a short description of the history, heritage, present situation, problems and hopes of the Malabar Church of St. Thomas the Apostle.